2018
DOI: 10.1111/1468-2427.12625
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Pattern of Residential Mobility in Guangzhou, China

Abstract: In urban China, residential mobility behaviors have changed fundamentally in recent decades. While research has been undertaken on the trends and causes of residential relocation for different population groups, less attention has been paid to micro‐level processes of residential change, yet the latter underscore urban dynamics. This study addresses this through a survey conducted in Guangzhou in late 2012, which analyzes the spatial flows of residential shifts within and between three distance zones—inner cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 60 publications
(100 reference statements)
1
20
0
1
Order By: Relevance
“…It is reported that relatively broad and distorted peak shapes were observed for iCIEF separation of PEGylated proteins. Modification of pharmalyte contents, methylcellulose concentration, protein concentration, focusing time, and addition of other additives could not yield reasonable peak shapes . Similarly, we found that the charge variants of PEGylated proteins merge into one broad peak during IEF, most likely due to masking of the protein by the surrounded PEG chain as well as the increased hydrodynamic volume .…”
Section: Introductionmentioning
confidence: 73%
“…It is reported that relatively broad and distorted peak shapes were observed for iCIEF separation of PEGylated proteins. Modification of pharmalyte contents, methylcellulose concentration, protein concentration, focusing time, and addition of other additives could not yield reasonable peak shapes . Similarly, we found that the charge variants of PEGylated proteins merge into one broad peak during IEF, most likely due to masking of the protein by the surrounded PEG chain as well as the increased hydrodynamic volume .…”
Section: Introductionmentioning
confidence: 73%
“…Several categories refer to ‘locals’ (registered in Shanghai), while ‘migrants’ are persons registered in other provinces. Previous studies deal only with this local‐versus‐migrant dichotomy, but it is informative to distinguish between locals living in their registered subdistrict and those living elsewhere in the city (Huang and Jiang, 2009; Li and Mao, 2019). We studied three categories based on location: migrants (39%), fixed locals (living in their registered subdistrict, 45%) and local movers (16%).…”
Section: Methodsmentioning
confidence: 99%
“…Research on residential mobility cannot be separated from the larger context within which it takes place (Li & Mao, 2019). The unprecedented changes that Chinese cities have experienced in recent decades are different from the prevailing conditions in Western countries (Cui, 2012; Lee, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In China, during the socialist era, residential mobility was uncommon because of the welfare housing allocation system and lifetime employment (Huang & Deng, 2006; Li & Mao, 2019). At the beginning of China's reform and opening up in the 1980s, industries were relocated, a large number of residential areas were built in the urban fringe and the population in the central areas of cities gradually began to move out (Zhou, 1996).…”
Section: Theoretical Frameworkmentioning
confidence: 99%